Sonographic evaluation of testicular volume in neonates in Ibadan, Nigeria (2015)
Background: The testes are responsible for the production of spermatozoa and testosterone in man. Relaible and accurate determination of testicular volumes is of great potential benefit in evaluation of patients with a variety of disorders affecting testicular growth, development and function. Ultrasonography (USS) provides a good and reliable tool for determining testicular volume when objective, accurate and reproducible measurements are required. This can be done in an easy and patients friendly manner. USS is readily available, cheap and does not invovle the use of ionizing radiation; hence its suitability in neonates.Aim:To determine the normal value for mean testicular volume in neonates using ultrasonography and to correlate testicular volume with weight, gestational age, and length as well as body mass index, so as to have a baseline reference value which will aid in prompt identification of neonates with testicular abnormalities for further evaluation and timely intervention. Design of the study: A multi-centre prospective cohort study. Study Setting: Radiology departments of the Univeristy College Hospital, Adeoyo General hospital and Eleta Catholic Hospital, Ibadan, Southwestern Nigeria. Materials & Methods: A total of 411 healthy male neonates had testicular ultrasound performed in the labor wards and post natal wards of the University College Hospital, Adeoyo General Hospital and Eleta Catholic Hospital, Ibadan, Nigeria. Testicular mean volume was obtained using the Lambert formular (length x width X height x 0.71). The statistical package for the Social Sciences (SPSS) for windows version 17.0 was used to analyze the data obtained. Results: The mean left testicular volume in this study was 0.276cm3+ 0.08925 while the mean right testicular volume was 0.278cm3+0.09233. The overall mean testicular volume in neonates was 0.28+ 0.09cm3no significant difference between the right and the left testes (p=0.000). There is a weak but statistically significant positive correlation between testicular volume and the birth weight, height, and body mass index but no correlation between the testicular volume and the gestational age at delivery. Conclusion: This study showed that the mean testicular volume was 0.28+0.09ml with no significant difference between the right and the left testes. There was a positive correlation between the birth weight, height and the body mass index and the volume of the right and the left testes but no correlation between the testicular volume and the gestational age of the neonates